Language Learning: What Factors May Influence It - Yuwinda Yuwinda; Syukur Insani (Journal of English Language Teaching and Linguistics, 2018)
As English is an international language, learning English nowadays has become a great deal to be taught in school, especially for the society whose English is their second or foreign language. However, learning English may be a psychological burden for learners, particularly learners learning English as a Foreign Language (EFL). Further, the issue in Second Language Acquisition (SLA) field is that although everyone has the same innate language processing mechanisms, certain individual characteristics affect how much individual learners use their processor to learn the language. Some of the learners acquire rapidly through the initial stages of learning a new language while others have repeated failures or meet with very slow progress with limited success. Therefore, it stands to reason that some of them might be anxious in learning L2. Pointing out the effect of anxiety in second or foreign language learning, there are still many other factors that should be taken into consideration to counterpart that issue, such as learners’ age, motivation, learning strategies and learning styles to be considered for enhancing language learning. Moreover, this paper aims to provide other factors that may contribute in acquiring language in a different point of views.